State and Economy during Indonesia’s Transition to Sovereignty: A Comparison with the Philippines, Singapore, South Korea, and Taiwan - Thee Kian Wie (Lembaran Sejarah, 2013)
This article discusses the role of the state and the economy in the transition from colonial rule to sovereignty in Indonesia in comparison with four other East Asian countries: the Philippines, Singapore, South Korea and Taiwan. Of all these fve countries, Indonesia’s economic performance during the early 1950s was satisfactory, but very poor during the early 1960s. Of the four other East Asian countries, economic prospects of the Philippines during the early independence period appeared most promising, as it was the frst Southeast Asian country embarking on industrialization. However, during the next few decades the Philippines’ economy faltered, as the state was wrecked by political instability and rebellions by communist and Moslem insurgents. By contrast, because of strong and far-sighted leadership Singapore, South Korea and Taiwan were capable of realizing rapid growth fuelled by rapid export-oriented industrialization.